Pengujian Karakteristik Limbah Pasir PLTP Dieng Sebagai Bahan Pengisi Isolator Resin Epoksi Silane - Abdul Syakur; Tumiran Tumiran; Hamzah Berahim; Rochmadi Rochmadi (Universitas Syiah Kuala, 2011)
Epoxy resin has been developed as an insulator material on the distribution and transmission line. In its development, the basic composition of DGEBA epoxy resin with MPDA as hardener is hydrophilic. Silane is added to improve the surface properties of materials to be more hydrophobic. To reduce the volume of epoxy resin as base material, silica sand from PLTP Dieng is added as filler. This paper presents the results of research on the effect of adding the composition of silica materials from PLTP Dieng upon silane epoxy resin sample to the value of the dielectric loss factor, contact angle and leakage current. Samples were prepared with a sample size 120mm x 50mm x 5mm. Material is composed of DGEBA, MPDA, silanes and silica with a various composition. Sample codes were 10%, 20%, 30%, 40% and 50%. Contact angle and leakage current were carried out according with IEC 587:1984 standards. Measurement of the dielectric loss factor (Tan ) was carried out at the Laboratory of High Voltage Engineering, PT. PLN (Persero) Electricity RD, Duren Tiga Jakarta, using a measuring instrument series M4100 Insulation Analyzer Instrument. The electrodes used in these measurements have diameter of 2.5 cm and 5 cm. The results showed that the composition of silica materials PLTP Dieng upon silane epoxy resin samples affect the value of dielectric loss factor. Based on the results of the measurement, it is concluded that the higher composition of silica materials, the higher value of dielectric loss factor are. Based on these results, it is suggested that the use of silica as a filler must consider the effect on the value of dielectric loss factor. When the dielectric loss factor is high, then the losses in the dielectric material is also high.